Comparative Transcriptome Profiling of the Loaches Triplophysa bleekeri and Triplophysa rosa Reveals Potential Mechanisms of Eye Degeneration - Zhao, Qingyuan; Zhang, Renyi; Xiao, Yingqi; Niu, Yabing; Shao, Feng; Li, Yanping; Peng, Zuogang (Frontiers in Genetics, 2020)
Eye degeneration is one of the most obvious characteristics of organisms restricted to subterranean habitats. In cavefish, eye degeneration has evolved independently numerous times and each process is associated with different genetic mechanisms. To gain a better understanding of these mechanisms, we compared the eyes of adult individuals of the cave loach Triplophysa rosa and surface loach Triplophysa bleekeri. Compared with the normal eyes of the surface loach, those of the cave loach were found to possess a small abnormal lens and a defective retina containing photoreceptor cells that lack outer segments. Sequencing of the transcriptomes of both species to identify differentially expressed genes (DEGs) and genes under positive selection revealed 4,802 DEGs and 50 genes under positive selection (dN/dS > 1, FDR < 0.1). For cave loaches, we identified one Gene Ontology category related to vision that was significantly enriched in downregulated genes. Specifically, we found that many of the downregulated genes, including pitx3, lim2, crx, gnat2, rx1, rho, prph2, and β|γ-crystallin are associated with lens/retinal development and maintenance. However, compared with those in the surface loach, the lower dS rates but higher dN rates of the protein-coding sequences in T. rosa indicate that changes in amino acid sequences might be involved in the adaptation and visual degeneration of cave loaches. We also found that genes associated with light perception and light-stimulated vision have evolved at higher rates (some genes dN/dS > 1 but FDR > 0.1). Collectively, the findings of this study indicate that the degradation of cavefish vision is probably associated with both gene expression and amino acid changes and provide new insights into the mechanisms underlying the degeneration of cavefish eyes.